The Effect of Environmental Performance on Financial Performance with Islamic Corporate Social Responsibility (ICSR) as Intervening Variable - Ersi Sisdianto; Mohd Shahril Ahmad Razimi; Rubhan Masykur; Rita Diana Mei Sari; Anton Robiansyah (Universitas Pendidikan Ganesha, 2023)
Islamic Corporate Social Responsibility (ICSR) is one of the efforts to reduce social problems that occur in society, by encouraging community productivity and creating justice. This study aims to analyze the effect of environmental performance on financial performance with Islamic Corporate Social Responsibility (ICSR). This research uses quantitative research. The population in this study is mining companies listed on the Indonesian Sharia Stock Index (ISSI) from 2016 to 2020. The sampling technique used in this study uses a purposive sampling technique. The number of samples in this study is 15 companies. The type of data used is secondary data in the form of financial reports and annual reports obtained through the official website of the Indonesia Stock Exchange and the official website of the related company. The dependent variable in this study is financial performance, while the independent variable is environmental performance. The data analysis method used is path analysis with the help of the Smart-PLS 3.0 application program. This study shows that environmental performance has an effect on financial performance, while Islamic Corporate Social Responsibility (ICSR) cannot mediate the relationship between environmental performance and financial performance.